SERVQUAL DAN IMPORTANCE-PERFORMANCE ANALYSIS UNTUK PERGURUAN TINGGI - Agus Hasan Pura A (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
When student do not focus solely on academic quality but focus on service quality too. It is essential for student perception of service quality to be evaluated and managed by the university. We can employ SERVQUAI and Important Performance Analysis methods to know the quality of service of the university. The information that result from application of these methods are very important for the university to improve the quality of service and what attribute should be concentrate to improve .